Effect of E-Log ' Behaviour of Compacted Fine Grained Soils Having Different Clay Mineralogy - H. S. Prasanna, Basavaraju (International Journal of Advanced Science and Technology, 2020)
Compressibility criteria of fine- grained soils possess a major challenge because of its complex physio chemical behavior due to the presence of clay mineral that it is kaolinite and otherMontmorillonite.Theconstruction sites having adequate safe bearing capacity and minimum degree of settlement it is facing major problems for the  industry at large to have constructions on compacted fine-grained soils having different clay mineralogy altogether.The structure constructed on such embankments have to be controlled effectively for settlements throughout the time .It is imperative that the compressibility behavior of compacted fine-grained soils with reference to clay mineralogy is having more qualitative approach. In the present research attempt has been made to study compressibility character of fine-grained soils having different clay mineralogy altogether .It is observed that the soils compacted for same placement densities for having different e-log sbehavior by virtue their different initial water contents.Equilibrium void ratio on wet side compacted state at any effective consolidation stress is always more than that the dry sides which highlights the role of placement conditions and soil fabric an  e-log sbehavior .Clay mineralogy place a vital role in the behavior of  an  e-log s curves .